PERMINTAAN KOPI INDONESIA: FAKTOR PENENTU DAN IMPLIKASINYA TERHADAP INDUSTRI KOPI - Paryanto, Edi (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
Coffee is a global commodity of high economic value and one of the most popular beverage ingredients in the world. Despite the challenges, such as climate change and farmer socio-economic issues, the coffee industry continues to adapt and find ways to meet the growing demand from global consumers. In Indonesia, coffee production tends to decrease but its consumption tends to increase, even higher than the growth of world coffee consumption. The increase in demand raises curiosity as to why this is happening. This research aims to identify what factors affect the demand for coffee in Indonesia. The research is a descriptive study with research locations in Indonesia selected using purposive due to demand coffee is high. The data used is secondary time series data from 1990–2022. Multiple regression analysis was applied with the amount of coffee demand as the dependent variable, and coffee prices (X1), international coffee prices (X2), tea prices (X3), and consumption per capita (X4) as the independent variables. The findings show that: 1) the factors studied jointly affect coffee demand in Indonesia at the 95% confidence level with a coefficient of determination (R square) of 0.997; 2) according to the partial analysis results at the 95% confidence level, not all variables have a significant effect on the consumption variable. Coffee prices (X 1) has no significant effect on the demand for coffee commodities, meanwhile tea prices (X 2) (substitute goods), international coffee prices (X 3), and consumption per capita (X 4) have significant effect on the demand for coffee commodities.  The key to increasing demand for coffee at the national level is a business strategy that is flexible and adaptive to international price fluctuations, as well as investing in increasing consumer awareness and preferences.